The Comparison of Flexural Performance of Reinforced Concrete Beam With Lap Splice and Threaded Coupler-Type Mechanical Splices - Zaneta Ambarwati; Jafar Jafar (Universitas Tribhuwana Tunggadewi Malang, 2022)
In the construction world, there are several ways to connect reinforcement: lap splice, welding, and mechanical. This study compares the flexural performance of reinforced concrete beams where the reinforcement is connected by lap splice and mechanical threaded coupler type. The size of the reinforced concrete beam used as the test object is 200×300×2000 mm, with an f'c value of 25 MPa. Three test specimen beams were prepared in this study: beams without reinforcement joints beams with lap joints, and beams with mechanical joints. From the laboratory tests, the nominal moment values (Mn) for reinforced concrete beams with lap joints and mechanical coupler-type connections were 42.231 MPa and 29.436 MPa, respectively. The maximum load is on the beam with lap joints of 138.85 kN. From the nominal moment value and maximum load obtained, it can be seen that the beam with lap joints can bear the most significant load. Regarding ductility, beams with coupler connections tend to be more brittle (non-ductile) when compared to beams with lap joints. Therefore, although the coupler-type mechanical connection has benefits, it has yet to be able to replace the lap joints in reinforced concrete beams in terms of strength and ductility. Mechanical connection failure occurred in the reinforcement section, which was turned to connect with the coupler.ABSTRAKDalam dunia konstruksi terdapat beberapa cara untuk menyambung tulangan yakni dengan cara penyaluran lewatan (Lap Splice), pengelasan (welded), dan mekanis. Penelitian ini membandingkan kinerja lentur balok beton bertulang dimana tulangannya disambung dengan cara penyaluran lewatan (Lap Splice) dan mekanis tipe threaded coupler. Ukuran balok beton bertulang yang digunakan sebagai benda uji adalah 200×300×2000 mm dengan nilai f’c 25 MPa. Tiga balok benda uji disiapkan dalam penelitian ini yakni, balok tanpa sambungan tulangan, balok dengan sambungan lewatan, dan balok dengan sambungan mekanis. Dari pengujian laboratorium yang dilakukan didapatkan nilai momen nominal (Mn) untuk balok beton bertulang dengan sambungan lewatan dan sambungan mekanis tipe coupler berturut-turut sebesar 42,231 MPa, dan 29,436 MPa. Beban maksimum terdapat pada balok dengan sambungan lewatan yakni sebesar 138,85 kN. Dari nilai momen nominal dan beban maksimum yang diperoleh dapat dilihat bahwa balok dengan sambungan lewatan dapat menanggung beban terbesar. Dari segi daktilitas, balok dengan sambungan coupler cenderung lebih getas (tidak daktail) jika dibandingkan dengan balok dengan sambungan lewatan. Oleh karena itu, meskipun sambungan mekanis tipe coupler memiliki benefit, namun belum mampu menggantikan sambungan lewatan pada balok beton bertulang dari segi kekuatan dan daktilitas. Kegagalan sambungan mekanis terjadi pada bagian tulangan yang dibubut untuk keperluan penyambungan dengan coupler.